Survey of resource management techniques in fog computing - Usha, Vadde; Vijaya Sri Kompalli, Dr. (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) generates large volume of data. Todayâ€™s Cloud models offer scalability, reliability and cost effectiveness. However the large volume, variety and velocity of data that is being generated by IoT devices challenges the long delay links between cloud data center and IoT devices. Fog Computing is an extension to the cloud computing, introduced by CISCO is a distributed paradigm. The basic idea is to deploy Cloud Computing infrastructure closer to the things (sensors/smart devices) that produce and act on data. This fascinating concept brings together the latest technologies like Cloud, Edge, IoT etc. In Fog computing, resource management is an important factor for better utilization of available resources and also providing optimal service for IoT applications. This study focuses on the recent research works undertaken in the resource management area of Fog computing and also compares various edge computing paradigms. At the end, other issues that are left as future challenges are highlighted.Â Â